THE INFLUENCE OF THE ROLE OF IRRIGATED RICE FARMER GROUPS ON THE LEVEL OF FAMILY WELFARE IN SIDOMUKTI VILLAGE, BONE-BONE DISTRICT, NORTH LUWU REGENCY - Rizal, Muhamad; Qaiyimah, Dinil (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2025)
This research is quantitative research which is analyzed statistically and descriptively. The aim of this research is to present the influence of the role of irrigated rice farmer groups on family welfare in Sidomukti Village. Data collection was carried out through direct observation, distributing questionnaires and documentation. Data analysis techniques were carried out by scoring data from questionnaires, then processed with MS Excel software and IBM SPSS Statistics 29. The results of the research show that the there are 3 variables that have different results, Class and Learning Facilities (X1) has a negative effect due to lack of real involvement, while the Vehicle for Cooperation (X2) and Business Production Unit (X3) have a positive effect and contribute directly to farmer welfare. The information presented can be a consideration for the local government in determining strategic policies that will be implemented by the government. Keywords: Farmer Group, Level Welfare, Rice Farmer